Heritage trail mapping for megalithic stones using GIS for ecotourism purposes - Kong Teck Sieng; Oliver Valentine Eboy; LizalinKalang (Ankara University Faculty of Education Department Primary Education, 2020)
Tourism is an essential industry in Malaysia that significantly influences the economy by contributing to financing, foreign exchange, and marketing. Nowadays, many tourists choose ecotourism as the primary option to be used as a tourist destination. Cultural and Heritage Tourism are one of the types of ecotourism that can attract many tourists either from within or outside the country who love cultural heritage. One of the cultural heritages in our country that can be an ecotourism product is the megalithic culture. This culture is a tradition of worshipping large stones in the ancient society that is becoming extinct. By promoting the heritage trail with megalithic theme scan attract tourists to visit the megalithic stone sites. This study produces a megalithic stone heritage trail map for low and high capabilities that can be used as a tourism product for ecotourism in the interior of Sabah, Tambunan. The data used in this study were obtained through fieldwork in Tambunan. This heritage trail map was produced using buffer and kernel density analysis using GIS applications. This study's heritage trail can guide tourism development to increase ecotourism products in our country and help generate our country's economy. Besides, this ecotourism also helps essential to protect nature from being damaged. At the same time, it also preserves the almost extinct megalithic stone cultural heritage in our country.